2020
DOI: 10.1097/adm.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Contraceptive Needs of Women Who Inject Drugs in Orange County: A Qualitative Study

Abstract: Objectives: Women with opioid use disorder experience higher rates of unintended pregnancy compared with the general US population. Our aim was to examine the factors that may affect access to desired contraception for women who use injection drugs. Methods: Using purposive sampling, we conducted semi-structured interviews pertaining to contraceptive use with 14 women ages 18 to 44 who were current users of injection drugs living in Orange County, CA be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Four studies identified concerns related to LARC placement or removal, including: concerns about the insertion or removal process ( Matusiewicz et al, 2017 ), fear of pain during insertion ( Rey et al, 2020 ), concerns about forgetting when to remove a method and potential fertility effects ( Sobel et al, 2021 ), and not wanting foreign objects in the body ( Rey et al, 2020 ) or in a particular location in the body ( Rey et al, 2020 , Smith et al, 2019 ). Method maintenance, including having to remember appropriate use ( Florsheim et al, 2020 ) or to take a daily pill ( Sobel et al, 2021 ), were barriers for HC methods, whereas not having control over starting and stopping the method was a LARC barrier ( Rey et al, 2020 ). Lack of knowledge ( Matusiewicz et al, 2017 , Meschke et al, 2018 , Rey et al, 2020 , Smith et al, 2019 ) or having enough knowledge ( Heil et al, 2016 ) about contraception were consistent barriers, as were having past negative experiences with contraception related to method failure ( Bornstein et al, 2019 , Florsheim et al, 2020 ), side effects ( Bornstein et al, 2019 ), appropriate storage and use ( Florsheim et al, 2020 ), and complications ( Smith et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies identified concerns related to LARC placement or removal, including: concerns about the insertion or removal process ( Matusiewicz et al, 2017 ), fear of pain during insertion ( Rey et al, 2020 ), concerns about forgetting when to remove a method and potential fertility effects ( Sobel et al, 2021 ), and not wanting foreign objects in the body ( Rey et al, 2020 ) or in a particular location in the body ( Rey et al, 2020 , Smith et al, 2019 ). Method maintenance, including having to remember appropriate use ( Florsheim et al, 2020 ) or to take a daily pill ( Sobel et al, 2021 ), were barriers for HC methods, whereas not having control over starting and stopping the method was a LARC barrier ( Rey et al, 2020 ). Lack of knowledge ( Matusiewicz et al, 2017 , Meschke et al, 2018 , Rey et al, 2020 , Smith et al, 2019 ) or having enough knowledge ( Heil et al, 2016 ) about contraception were consistent barriers, as were having past negative experiences with contraception related to method failure ( Bornstein et al, 2019 , Florsheim et al, 2020 ), side effects ( Bornstein et al, 2019 ), appropriate storage and use ( Florsheim et al, 2020 ), and complications ( Smith et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Method maintenance, including having to remember appropriate use ( Florsheim et al, 2020 ) or to take a daily pill ( Sobel et al, 2021 ), were barriers for HC methods, whereas not having control over starting and stopping the method was a LARC barrier ( Rey et al, 2020 ). Lack of knowledge ( Matusiewicz et al, 2017 , Meschke et al, 2018 , Rey et al, 2020 , Smith et al, 2019 ) or having enough knowledge ( Heil et al, 2016 ) about contraception were consistent barriers, as were having past negative experiences with contraception related to method failure ( Bornstein et al, 2019 , Florsheim et al, 2020 ), side effects ( Bornstein et al, 2019 ), appropriate storage and use ( Florsheim et al, 2020 ), and complications ( Smith et al, 2019 ). Concerns that contraception would cause infertility ( Bornstein et al, 2019 , Rey et al, 2020 , Smith et al, 2019 ); delay a desired future pregnancy ( Bornstein et al, 2019 , Smith et al, 2019 ); and physically or psychologically interfere with sex ( Rey et al, 2020 , Smith et al, 2019 ), the body’s natural processes ( MacAfee et al, 2020a ), and mood stabilizing medications ( Sobel et al, 2021 ) were barriers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations